Viabilidade da energia solar fotovoltaica: uma análise utilizando modelagem matemática na educação básica - Nunes, Lydia Soares de Barros (2024)
This research carried out in the area of Basic Education is based on the conception of mathematical modeling as a teaching-learning tool, by Rodney Carlos Bassanezi and Maria Salett Biembengut as Modelling. It seeks to identify the relationship between Mathematical Modelling and current curriculum documents, in addition to investigating the impact of the use of this teaching methodology in a class of 1º year of high school in Aparecida de Goiânia, Goiás, analyzing changes in the teaching-learning environment in relation to the interest of students in Mathematics classes of the contents addressed. The pedagogical proposal examines the feasibility of installing solar photovoltaic system in residences in the region, emphasizing environmental and financial issues. This research adopts a qualitative approach, divided into two stages. Initially, a bibliographical research was carried out on Mathematical Modelling, the documents os the National Base Comum Curricular, and the Curriculum Document of Goias for high School, in addition to forms of power generation, especially hydroelectric and solar photovoltaic. Based on the information collected, a didactic sequence was elaborated, addressing the contents of functions and financial mathematics. The second stage of the research involves participant observation during the implementation of the planned classes. The study aims to highlight the potential and challenges of the use of Mathematical Modelling as a teaching methodology in Basic Education, relating theory and practice.